Infection-related hospital isolation and social outcomes: A systematic review of family presence, communication modalities, and patient-reported measures - Dalibor Sedláček; Alena Lochmannová; Robin Šín; Miroslav Kubiska; Petr Simbartl; Marie Kulová (Journal of Infection Prevention, 2026)
Background Pathogen transmission-based precautions are essential to safe inpatient care, yet loneliness and loss of social connection carry clinical consequences. Objective To synthesize evidence on the association between hospital isolation and patient-reported loneliness or social connectedness, and to identify interventions and routine processes that mitigate these effects. Method We conducted a systematic review under a prespecified methodological plan and reported it according to PRISMA 2020. We searched MEDLINE, Scopus, Web of Science, CENTRAL, Europe PMC, WHO Global Index Medicus, CINAHL and PsycINFO without design limits. Eligible designs were randomised/quasi-experimental, observational, qualitative, mixed methods and implementation. Outcomes were loneliness/connectedness and proximate processes (family presence, communication channel/cadence). We screened 717 records, assessed 18 full texts and included 16 studies. Results Across acute wards, adult intensive care, rehabilitation and paediatrics, isolation was associated with higher loneliness and perceived social avoidance on general wards. In intensive care and paediatrics, restricted presence disrupted connectedness, parental role and peer ties. Barrier precautions thinned spontaneous staff–patient contact and displaced key conversations to telephone/video. Interventions clustered in three families—brief education/coping supports, organized tele-visiting with scheduled video/phone, and age-appropriate digital/VR supports—with good feasibility/acceptability and improvements in patient-reported outcomes and anxiety/stress in several studies. Conclusions Isolation carries consistent social costs. Simple, proportionate countermeasures—shared, consistent explanations of purpose and predictable, resourced contact routines—are actionable now. Future work should test defined bundles using shared patient-reported and process outcomes in pragmatic designs.